Performance of early maize cultivars derived from recurrent selection for grain yield and Striga resistance - Badu-Apraku, Baffour; Lum, A.F.; Fakorede, M.A.B.; Menkir, A.; Chabi, Y.; The, C.; Abdulai, M.; Jacob, S.; Agbaje, S. (Wiley, 2008)
Maize (Zea mays L.) production in west and central Africa (WCA) is constrained by the parasitic weed Striga hermonthica (Del.) Benth and recurrent drought. Two early maize populations, TZE-W Pop DT STR C0 (white) and TZE-Y Pop DT STR C0 (yellow), developed from diverse genetic backgrounds, were subjected to three cycles of S1 recurrent selection under artificial Striga infestation. Inbreds and synthetic cultivars were developed from the different cycles of selection. The populations (C0), derived cultivars, and check cultivars were evaluated in 2002 and 2003 under Striga-infested and Striga-free environments in WCA. The objective was to assess the performance of the derived cultivars from the different cycles of selection. Under Striga infestation, ACR 94 TZE Comp5-Y and ACR 94 TZE Comp5-W, which were not from the selection program, were the highest-yielding group (2158 and 2124 kg ha−1, respectively). The second group comprised six products of the selection program, with grain yield ranging from 1806 to 1954 kg ha−1 The third group, with grain yield of 1498 to 1759 kg ha−1 contained mostly Striga-susceptible cultivars and the C0 of the selection program. Under Striga-free conditions, the performance of several cultivars from the selection program was equal to or better than ACR 94 TZE Comp5-Y and ACR 94 TZE Comp5-W. The genotype plus genotype × environment interaction biplot analysis demonstrated that EV DT-Y 2000 STR C1 and TZE-W Pop DT STR C3 from the selection program, along with ACR 94 TZE Comp5-W, had stable grain yield under Striga-infested and noninfested conditions.